NON -VERBAL BEHAVIOR - ITS PERCEPTION AND INTERPRETATION - E. T. Kenenbayev (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the stages and reasons for the study of non-verbal human behavior. Based on a number of characteristics of non-verbal behavior that differ from each other in the scientific literature, it is concluded that they are insufficiently studied and that it is necessary to take into account different opinions on this issue in their research activities.